Analysis of radon-associated squamous cell carcinomas of the lung for a p53 gene hotspot mutation - Yang, Qin; Bartsch, Helmut; Wegener, Kurt; Hollstein, Monica (British journal of cancer, 2000)
Squamous cell lung carcinomas (SCC) from former employees of the Wismut uranium mining company (Saxony, Germany) were obtained from the Stollberg Archive in order to screen for p53 tumour suppressor gene codon 249 arg→met hotspot mutations, a putative molecular bio-dosimeter of alpha-particle (radon) exposure (Taylor et al (1994) Lancet: 86-87; McDonald et al (1995) Cancer Epidemiol Biomarkers Prevent 4: 791-793). Of the 29 archived samples of SCC meeting quality criteria for DNA analysis by polymerase chain reaction (PCR) and Hae III restriction enzyme digestion, two tumours were found that harboured this mutation. DNA sequencing confirmed the presence of a G to T base substitution within the Hae III site spanning codons 249 and 250 of the p53 gene that results in replacement of arginine (wild-type) by methionine at residue 249. When these data are combined with those from our previous study of tumours from the Stollberg Archive in which 50 lung tumours were examined, (including nine SCCs), we conclude that the G→T (arg→met) codon 249 mutation prevalence in the Wismut miner cohort is not sharply elevated in lung cancers in general (two mutations/79 tumours), or specifically in SCCs of the lung (two mutations/38 SCC) when compared to data from lung cancer patients with no reported occupational exposure to radon gas. © 2000 Cancer Research Campaign
Gesehen am 02.02.2021